Uji Ketahanan Beberapa Varietas Tomat terhadap Penyakit Layu Fusarium (Fusarium oxysporum f. sp. lycopersici) - Tjut Chamzurni; M. Abduh Ulim; Edi Dianur (Jurnal Agrista, 2010)
Resistency of Tomatoes Varieties on Fusarium wilt Disease (Fusarium oxysporum f. sp. lycopersici)ABSTRACT. Tomato plants are herbaceous annual plant, having hermaphrodite  flowers and are suitable to be planted in a cold area. Wilt disease is one of the important disease of tomato plants which is caused by Fusarium oxysporum f. sp. lycopersici (fol). This disease can cause a great loss to the tomato producing in many regions in the world 20%-30%. A study has been conducted the resistance of several varieties of tomato plants against Fusarium wilt disease caused by Fusarium oxysporum f. sp. lycopersici. The tomato varieties observed were Local Aceh, Jelita, Permata, Sakata and Lentana. The results showed that Local Aceh variety and Jelita variety were highly  resistant to Fusarium wilt disease. The other 3 varieties showed a lower level of resistance to the wilt disease compared to those of Local Aceh and Lentana variety.